The effects of psychiatric disorders on the risk of chronic heart failure: a univariable and multivariable Mendelian randomization study - Yang Chen; Yang Chen; Wenke Peng; Wenke Peng; Min Pang; Min Pang; Botao Zhu; Botao Zhu; Huixing Liu; Huixing Liu; Die Hu; Die Hu; et al. (Frontiers Media S.A., 2024)
BackgroundSubstantial evidence suggests an association between psychiatric disorders and chronic heart failure. However, further investigation is needed to confirm the causal relationship between these psychiatric disorders and chronic heart failure. To address this, we evaluated the potential effects of five psychiatric disorders on chronic heart failure using two-sample Mendelian Randomization (MR).MethodsWe selected single nucleotide polymorphisms (SNPs) associated with chronic heart failure and five psychiatric disorders (Attention-Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD), Major Depression, Bipolar Disorder and Schizophrenia (SCZ)). Univariable (UVMR) and multivariable two-sample Mendelian Randomization (MVMR) were employed to assess causality between these conditions. Ever smoked and alcohol consumption were controlled for mediating effects in the multivariable MR. The inverse variance weighting (IVW) and Wald ratio estimator methods served as the primary analytical methods for estimating potential causal effects. MR-Egger and weighted median analyses were also conducted to validate the results. Sensitivity analyses included the funnel plot, leave-one-out, and MR-Egger intercept tests. Additionally, potential mediators were investigated through risk factor analyses.ResultsGenetically predicted heart failure was significantly associated with ADHD (odds ratio (OR), 1.12; 95% CI, 1.04-1.20; p = 0.001), ASD (OR, 1.29; 95% CI, 1.07-1.56; p = 0.008), bipolar disorder (OR, 0.89; 95% CI, 0.83-0.96; p = 0.001), major depression (OR, 1.15; 95% CI, 1.03-1.29; p = 0.015), SCZ (OR, 1.04; 95% CI, 1.00-1.07; p = 0.024). Several risk factors for heart failure are implicated in the above cause-and-effect relationship, including ever smoked and alcohol consumption.ConclusionOur study demonstrated ADHD, ASD, SCZ and major depression may have a causal relationship with an increased risk of heart failure. In contrast, bipolar disorder was associated with a reduced risk of heart failure, which could potentially be mediated by ever smoked and alcohol consumption. Therefore, prevention strategies for heart failure should also incorporate mental health considerations, and vice versa.